Dentistry Insights: Single-Walled and Multi-Walled Carbon Nanotubes, Carbon Dots, and the Rise of Hybrid Materials - Roxana-Ionela Vasluianu; Ana Maria Dima; Livia Bobu; Alice Murariu; Ovidiu Stamatin; Elena-Raluca Baciu; Elena-Odette Luca (Journal of Functional Biomaterials)
We are committed to writing this narrative review given that carbon-based nanomaterials are revolutionizing dental medicine. Since the groundbreaking discovery of carbon nanotubes in 1991, their dental applications have skyrocketed. The numbers speak for themselves: in 2024, the global carbon nanotubes market hit USD 1.3 billion and is set to double to USD 2.6 billion by 2029. Over the past few decades, various forms of carbon nanomaterials have been integrated into dental practices, elevating the quality and effectiveness of dental treatments. They represent a transformative advancement in dentistry, offering numerous benefits such as augmented mechanical properties, antimicrobial activity, and potential for regenerative applications. Both carbon nanotubes (CNTs) and carbon dots (CDs) are derived from carbon and integral to nanotechnology, showcasing the versatility of carbon nanostructures and delivering cutting-edge solutions across diverse domains, such as electronics, materials science, and biomedicine. CNTs are ambitiously examined for their capability to reinforce dental materials, develop biosensors for detecting oral diseases, and even deliver therapeutic agents directly to affected tissues. This review synthesizes their current applications, underscores their interdisciplinary value in bridging nanotechnology and dentistry, identifies key barriers to clinical adoption, and discusses hybrid strategies warranting further research to advance implementation.